2016
DOI: 10.1097/cmr.0000000000000254
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns of adjuvant interferon-α2b for high-risk melanoma: a retrospective study of the Grupo Español Multidisciplinar de Melanoma – Prima study

Abstract: Adjuvant interferon-α2b (IFN-α2b) has been studied extensively in clinical trials, but there have been few studies of real-world use. The aim of this study is to describe the IFN-α2b real-world patterns in patients with high-risk melanoma in Spain. This was a retrospective and multicentre chart review study of an unselected cohort of patients with melanoma at high risk for relapse (stage IIB/IIC/III) treated with IFN-α2b. Patterns were assessed in terms of dose and compliance to planned treatment. A survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…This variation in treatment schedules aligns with prior studies, for example, a multicountry retrospective and prospective observational study found that 33% of patients with stage IIIB/C melanoma who were treated with high-dose IFN experienced a dose delay and/or reduction, and 29% discontinued therapy [44]. Similarly, results from another retrospective study reported modifications in both induction and maintenance schedules in 38 and 28% of patients, respectively [45]. The variability in treatment dose, schedule and duration, has resulted in a lack of clear insight regarding the risk benefit to patients [46,47].…”
Section: Discussionsupporting
confidence: 78%
“…This variation in treatment schedules aligns with prior studies, for example, a multicountry retrospective and prospective observational study found that 33% of patients with stage IIIB/C melanoma who were treated with high-dose IFN experienced a dose delay and/or reduction, and 29% discontinued therapy [44]. Similarly, results from another retrospective study reported modifications in both induction and maintenance schedules in 38 and 28% of patients, respectively [45]. The variability in treatment dose, schedule and duration, has resulted in a lack of clear insight regarding the risk benefit to patients [46,47].…”
Section: Discussionsupporting
confidence: 78%
“…The anti-tumor effect of IFN-a is expected to be induced by CD8+ T cell-mediated autologous tumor cell lysis. High-dose IFN is currently the standard adjuvant therapy, despite the high incidence of adverse events (Espinosa et al, 2016). The significant clinical efficacy of oncolytic virus (Andtbacka et al, 2015) and toll-like receptor agonist (Mauldin et al, 2015) had opened up a new path for melanoma immunotherapy, and follow-up clinical research is underway.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important factors limiting the large-scale application of IFN-α2b in treating malignancy is the prevailing adverse effects, although they are not life-threatening in most cases. In a retrospective study of melanoma, 71% of the patients were found to experience at least one kind of adverse effect, but no drug-related death was observed [ 251 ]. Another study on Sézary syndrome reported a similar percentage of patients who experienced a toxic response (60%) [ 196 ].…”
Section: Introductionmentioning
confidence: 99%